Les droits et obligations de l’assuré - Letourneau, Alain (Assurances, 1996)
We are grateful to the author, Mr. Alain Letourneau and the organizer, the firm Insight, for authorizing us to publish a very interesting reflection on the rights and obligations of the insured. The author examines the commitments of insurers notably under the escape, excess and super escape clauses. In cases of double insurance, courts unanimously agree that no insured must be left without coverage. Insurers are required to indemnify the insured and find a way to share the cost among themselves.